Performance Management Analysis of Employees at PT Indofood Sukses Makmur Tbk - Wahidah, Roisatul; Ningsih, Widya Kurniawati; Sentot Imam Wahjono (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Abstract Employee performance management is one of the important aspects in increasing the productivity and effectiveness of an organization. This study aims to analyze the performance management system implemented at PT Indofood Sukses Makmur Tbk, a large company engaged in the food and beverage industry. This study uses a qualitative approach with a case study method, which involves in-depth interviews with HR managers and analysis of company policy documents. The results of the study indicate that PT Indofood Sukses Makmur Tbk has implemented a comprehensive performance management system, which includes performance planning, monitoring, evaluation, and employee development. However, there are several challenges related to the objectivity of performance assessments and communication between superiors and subordinates. This study provides recommendations for increasing transparency in the performance assessment process and training for managers in providing constructive feedback. Keywords: Performance Management, Employees, PT Indofood Sukses Makmur Tbk, Performance Evaluation, Employee Development